Lagrangian coherence and source of water of Loop Current Frontal Eddies in the Gulf of Mexico. (November 2022) - Hiron, Luna; Miron, Philippe; Shay, Lynn K.; Johns, William E.; Chassignet, Eric P.; Bozec, Alexandra
Highlights: Loop Current Frontal Eddies are formed by the convergence of Gulf of Mexico water. Once formed, Loop Current Frontal Eddies can remain Lagrangian coherent for weeks. Loop Current Frontal Eddies are Lagrangian coherent from the surface down to 560 m. Large Loop Current Frontal Eddies modify the flow and the transport of oil and tracers. Abstract: Loop Current Frontal Eddies (LCFEs) are known to intensify and assist in the Loop Current (LC) eddy shedding. In addition to interacting with the LC, these eddies also modify the circulation in the eastern Gulf of Mexico by attracting water and passive tracers such as chlorophyll, Mississippi freshwater, and pollutants to the LC-LCFE front. During the 2010 Deepwater Horizon oil spill, part of the oil was entrained not only in the LC-LCFE front but also inside an LCFE, where it remained for weeks. This study assesses the ability of the LCFEs to transport water and passive tracers without exchange with the exterior (i.e., Lagrangian coherence) using altimetry and a high-resolution model. The following open questions are answered: (1) How long can the LCFEs remain Lagrangian coherent at and below the surface? (2) What is the source of water for the formation of LCFEs? (3) Can the formation of Lagrangian coherent LCFEs attract shelf water? Strong frontal eddies leading to LC eddy shedding are investigated using a 1-km resolution model for the Gulf of Mexico and altimetry. The results show that LCFEs are composed of waters originating from the outer band of the LC front, the region north of the LC, and the western West Florida Shelf and Mississippi/Alabama/Florida shelf, and potentially drive cross-shelf exchange of particles, water properties, and nutrients. At depth (≈180 m), most LCFE water comes from the outer band of the LC front in the form of smaller frontal eddies. Once formed, LCFEs can transport water and passive tracers in their interior without exchange with the exterior for weeks: these eddies remained Lagrangian coherent for up to 25 days in the altimetry dataset and 18 days at the surface and 29 days at depth (≈180 m) in the simulation. LCFE can remain Lagrangian coherent up to a depth of ≈ 560 m. Additional analyses show that the LCFE involved in the Deepwater Horizon oil spill formed from water near the oil rig location, in agreement with previous studies. Temperature-salinity diagrams from a high-resolution model and aircraft expendable profilers show that LCFEs are composed of Gulf of Mexico water as opposed to LC water. Therefore, LCFE formation and propagation actively modify the surrounding circulation and affect the evolution of the flow and the transport of oil and other passive tracers in the Eastern Gulf of Mexico.